2018
DOI: 10.1021/acs.macromol.8b01742
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Thermal Properties and Morphology of Isodimorphic Poly[(butylene succinate)-ran-(ε-caprolactone)] Copolyesters by Changing Composition, Molecular Weight, and Thermal History

Abstract: Tuning the thermal properties and morphology of isodimorphic poly[(butylene succinate)-ran-(ɛ-caprolactone)] copolyesters by changing composition, molecular weight and thermal history

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 43 publications
7
78
0
Order By: Relevance
“…The pseudo-eutectic sample, MM W -BS 45 CL 55 , exhibits a very particular phase behavior, one or both phases can be formed depending on the crystallization conditions (via nonisothermal or isothermal crystallization) [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pseudo-eutectic sample, MM W -BS 45 CL 55 , exhibits a very particular phase behavior, one or both phases can be formed depending on the crystallization conditions (via nonisothermal or isothermal crystallization) [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the phase diagram of HM W -BS x CL y copolyesters. This series of random high-molecular-weight copolymers display similar calorimetric properties to medium-molecular-weight BS x CL y [ 37 ]. They show a single-phase melt and a single glass transition temperature and, upon cooling from the melt, the materials crystallize over the entire composition range as confirmed by X -ray diffraction studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PBS and PCL are semicrystalline polymers whose thermal properties (melting temperature ( T m ) or glass transition temperature ( T g )) can be tuned by copolymerization. In fact, it has been found that poly(butylene succinate- co -ε-caprolactone) copolyester is crystalline for all compositions and crystallized isodimorphically for intermediate compositions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%